Graphite coating method and asphalt coated graphite

By using the three-step method of "low-temperature softening + aqueous solution washing + high-temperature carbonization" on the graphite negative electrode material, the problem of poor diffusion kinetics during high-power charging and discharging is solved, and the asphalt component content is controlled in stages, the rate performance and coking value are improved, and the plate cleavage condition and production cost are reduced, and it is suitable for large-scale industrial production.

CN119581519APending Publication Date: 2025-03-07WANHUA CHEM GRP BATTERY TECH CO LTD +2

Patent Information

Application Number
CN202411689613.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have poor diffusion kinetics during high-power charging and discharging, which is difficult to meet the demand for fast charging and high-current discharge of consumer electronic products. At the same time, the surface coating process has the problem of difficult coordination of the content of asphalt components.

Method used

The three-step method of "low-temperature softening + aqueous solution washing + high-temperature carbonization" is adopted to achieve stage-based control of the three-component content of asphalt coating agent, ensure the uniformity of the coating process and the coking value of the high-temperature section, reduce the degree of plate bonding, and avoid the residue and etching of organic polymer materials in graphite materials through aqueous solution detergent.

Benefits of technology

It improves the rate performance and coking value of graphite products, reduces the slab bonding situation and production costs, simplifies the process flow, reduces the emission of volatile pollutants, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150576850000061
    Figure BDA0005150576850000061
  • Figure HDA0005150576860000011
    Figure HDA0005150576860000011
  • Figure HDA0005150576860000012
    Figure HDA0005150576860000012
Patent Text Reader

Abstract

The invention belongs to the technical field of negative electrode materials, and particularly relates to a graphite coating method. By adopting a three-step method of low-temperature softening, aqueous solution washing and high-temperature carbonization, the staged control of the contents of the three components in the working procedures is realized, and the content of each component of the asphalt in each working procedure is always in the optimal ratio. According to the invention, the uniformity in the coating process can be ensured, the coking value can be increased, and the hardening degree of the material can be reduced, and the adopted aqueous solution detergent can also ensure the full reaction of the organic polymer material and the components in the asphalt, and does not remain in the graphite material, so that the negative gain effect is avoided. The method disclosed by the invention is simple in process flow, low in volatile pollutant emission, low in production cost and suitable for large-scale industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of negative electrode material technology, specifically relating to a method for graphite coating and graphite coated with pitch. Background Art

[0002] In recent years, consumer electronics products, represented by mobile phones, tablets, and drones, have played an increasingly important role in social production and people's lives. As an energy storage device supporting the large-scale application of electronic products, lithium-ion batteries have become a key research direction for many research institutes and related technology companies due to their high energy density, good power performance, and strong environmental adaptability.

[0003] For consumer electronics products, due to specific usage scenarios and customer experience requirements, devices often need to have relatively fast charging capabilities and instantaneous high-current discharge capabilities. To meet the urgent needs of the downstream market, the supporting lithium-ion batteries also need to have good power performance. Breaking this down to the material end, this requires the positive and negative electrode materials to have good rate performance. Compared with positive electrode materials such as ternary or lithium iron phosphate, negative electrode materials, due to their low potential, will experience a further decrease in potential when charged and discharged with a large current density. This leads to the elementalization of lithium ions on the negative electrode surface, thus causing battery safety issues. Currently, the most mainstream negative electrode material for lithium-ion batteries is graphite. Graphite is a typical layered two-dimensional material. Lithium ions can only be transported through the end faces in graphite crystals, gradually intercalating and deintercalating in a step-by-step manner. Therefore, the diffusion kinetics are poor, making it difficult to meet the requirements of high-power charging and discharging.

[0004] To address the poor rate performance of graphite anode materials, the industry currently employs two main optimization methods. The first method is to reduce the particle size. Since the diffusion coefficient of lithium ions depends on the diffusion distance and area, reducing the particle size can significantly improve the rate performance. Patent CN113851614A proposes a low-temperature fast-charging artificial graphite anode material and its preparation method, controlling the particle size D50 of the anode material to 3–8 μm, thus ensuring good high-current charge / discharge capability. However, smaller material size and larger specific surface area lead to lower electrode compaction density, poor processing performance, and increased electrochemical side reactions; therefore, particle size reduction needs to be controlled within a certain range. The second method is surface coating. Due to the good crystallinity of graphite and its small interlayer spacing, the industry typically uses coating agents such as asphalt or resin to coat its surface with soft or hard carbon at high temperatures. Soft and hard carbon have larger interlayer spacing and higher lithium potential, which can reduce the diffusion resistance of lithium ions. Patent CN118039828A proposes a method for graphite coating using an organic solution containing asphalt, resulting in a coated carbon layer of moderate thickness and improving the rate performance of the product. However, asphalt coating also faces significant technical bottlenecks. Based on their solubility in toluene / benzene and quinoline solvents, the substances in asphalt are mainly classified into three types: α-resin (QI), β-resin (TI), and γ-resin (TS). Among them, α-resin has the largest molecular weight and is mainly used to improve the coking value of asphalt; β-resin has a moderate molecular weight and is mainly used to improve the adhesion of asphalt; and γ-resin has the smallest molecular weight and is mainly used to lower the softening point of asphalt and provide fluidity.

[0005] For the surface coating process, the optimal asphalt exhibits good fluidity at low temperatures, enabling uniform coating of the graphite surface. However, excessive adhesion is undesirable, as it would cause material caking upon high-temperature heating, increasing energy consumption in the depolymerization equipment. Additionally, a high coking value is desirable, resulting in lower exhaust emissions and less environmental pressure at high temperatures. However, in asphalt production, high gamma resin content inevitably implies low alpha and beta resin content, resulting in good fluidity but low coking value. Conversely, high alpha resin content leads to poor fluidity and coating properties, while excessively low beta resin content results in weak adhesion. These two processes present inherently contradictory performance indicators.

[0006] To facilitate better and more uniform coating of asphalt, a large amount of organic solvents are typically used in the process. However, these solvents usually contain large amounts of benzene compounds or other harmful components, making them difficult to apply at low cost in both environmental protection and actual production, as illustrated by patents CN118039828A and JP2000003708A. Furthermore, organic solutions often exhibit low surface tension, making solid-liquid separation difficult. Residues can also condense into carbon at high temperatures, resulting in a decrease in the tap density of the finished product. Additionally, detergents can penetrate deep into the material's pores, further etching the material and leading to an increase in specific surface area, among other negative effects.

[0007] Therefore, meeting the surface coating requirements for asphalt, rationally controlling the content of each component in the asphalt during the process, and avoiding further negative effects on the main material are key improvement directions for improving coating quality and achieving excellent rate performance of materials. This is also one of the important solutions for high-power lithium-ion batteries. Summary of the Invention

[0008] This invention provides an asphalt coating agent for graphite products and a graphite coating method thereof. The invention employs a three-step method of "low-temperature softening + aqueous solution washing + high-temperature carbonization," achieving staged control of the content of the three components during the process. This method ensures uniformity during coating, increases the coking value at high temperatures, and reduces material caking. Furthermore, the aqueous solution detergent for the organic polymer material ensures sufficient reaction between the organic polymer material and the components in the asphalt, without leaving residues or etching in the graphite material.

[0009] The method of this invention has a simple process flow, low emissions of volatile pollutants, and can reduce investment costs for incinerators and environmental protection facilities. At the same time, the aqueous detergent can be recycled, resulting in low production costs and suitability for large-scale industrialization.

[0010] On one hand, the present invention provides a method for graphite coating, the method comprising the following steps:

[0011] S1. Micron-sized graphite is uniformly mixed with asphalt coating agent to obtain mixture A;

[0012] S2. Heat and stir mixture A, then cool to obtain intermediate product B;

[0013] S3. Intermediate product B is washed and dried with detergent to obtain intermediate product C;

[0014] S4. The intermediate product C is carbonized at high temperature, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0015] Furthermore, in step S1, the asphalt coating agent is composed of α resin (QI), β resin (TI), and γ resin (TS).

[0016] Furthermore, the content of α-resin (QI) in the asphalt coating agent is 1% to 15%.

[0017] Furthermore, the content of β resin (TI) in the asphalt coating agent is 14% to 50%.

[0018] Furthermore, the content of γ-resin (TS) in the asphalt coating agent is 35% to 85%.

[0019] Furthermore, the particle size D of the asphalt coating agent50 The preferred size is 2µm to 6µm.

[0020] Furthermore, in step S1, the mass ratio of asphalt coating agent to graphite is preferably 0.1 to 10:100, more preferably 0.5 to 5:100.

[0021] Furthermore, the heating temperature for low-temperature stirring in step S2 is T1 = 100-350℃, preferably 150-350℃.

[0022] Furthermore, the heating time for low-temperature stirring in step S2 is t1 = 60-300 min, preferably 100-280 min.

[0023] Furthermore, in step S2, the stirring rate of the low-temperature stirring is v1 = 30-120 r / min, preferably 45-120 r / min.

[0024] Furthermore, in step S3, the detergent contains water and an organic polymer material. The organic polymer material is soluble in or stably dispersed in water. Preferably, the organic polymer material is one or more of acrylic polymers, polyvinyl alcohol, polyacrylamide, and acrylate copolymers. The molecular weight of acrylic and acrylate polymers is between 1 million and 5 million, the molecular weight of polyacrylamide is between 5 million and 20 million, and the molecular weight of polyvinyl alcohol is between 80,000 and 120,000.

[0025] Furthermore, the mass percentage of organic polymer materials in the detergent in step S3 is preferably 1-45 wt%, more preferably 5-25 wt%.

[0026] Furthermore, in step S3, the mass ratio of detergent to intermediate product B is (10-100):1, preferably (10-50):1.

[0027] Furthermore, the stirring rate for stirring and washing in step S3 is v2 = 10-60 r / min, preferably 15-55 r / min.

[0028] Furthermore, the high-temperature carbonization temperature in step S4 is T2 = 800-1300℃, preferably 900-1250℃.

[0029] Furthermore, the high-temperature carbonization time in step S4 is t2 = 5 to 15 hours, preferably 6 to 12 hours.

[0030] Finally, the present invention provides bitumen-coated graphite prepared by the above method.

[0031] The asphalt coating agent for graphite products and its application method provided by this invention have the following advantages:

[0032] 1. This invention creatively adopts a three-step method of "low-temperature softening + aqueous solution washing + high-temperature carbonization" to achieve staged control of the content of the three components, ensuring that the content of each component of asphalt is always in the optimal ratio in each process.

[0033] 2. The method provided by this invention utilizes the principle of "like dissolves like," which can ensure the uniform coating of graphite products by asphalt without leaving residues or etching in the graphite material. At the same time, it can ensure the combination of polymer materials and γ-resin in asphalt, thereby increasing the coking value in the high-temperature section and reducing the degree of material caking.

[0034] 3. The method of the present invention has a simple process flow, does not use a large amount of toxic and harmful organic solvents, has low volatile content, and the aqueous solvent and dissolved oil phase can be naturally separated, reducing the investment cost of incinerators and environmental protection facilities. At the same time, the detergent will not have a negative beneficial effect on the product and can be recycled, resulting in low production cost and suitability for large-scale industrialization. Attached Figure Description

[0035] Figures 1-2 SEM images of the graphite products prepared in Example 1 and Comparative Example 1 of this invention.

[0036] Figures 3-4 These are TEM images of the graphite products prepared in Example 1 and Comparative Example 1 of the present invention.

[0037] Figure 5 This is a SEM image of the graphite product prepared in Comparative Example 3 of this invention. DETAILED DESCRIPTION

[0038] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to the following embodiments.

[0039] Raw materials and sources:

[0040] The asphalt coating agent used in this article was purchased from Liaoning Hongyu Carbon Graphite Materials Co., Ltd.

[0041] The organic polymer materials used in this article, such as acrylic polymers, polyvinyl alcohol, polyacrylamide, and acrylate copolymers, were all purchased from Beijing Innocare Technology Co., Ltd.

[0042] The graphite material used in this paper was prepared using a self-developed method. Specifically, it was obtained by pulverizing petroleum coke and then graphitizing it at high temperature, with a graphitization degree ≥92% and a powder compaction ≥1.78 g / cm³. 3 .

[0043] Test method:

[0044] The coking value in this paper was tested in accordance with the national standard GB / T 3521-2008 "Methods for Chemical Analysis of Graphite". The instrument was a high-temperature box-type resistance furnace, model SX2-8-13, with a temperature range of RT+5℃ to 1300℃.

[0045] The electrochemical performance tests in this paper were conducted in accordance with the national standard GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", and the testing equipment was the Xinwei CT-4000Q button cell tester.

[0046] The particle size was tested in accordance with the national standard GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", and the testing equipment was a Malvern 3000 particle size analyzer.

[0047] Example 1:

[0048] S1. D 50 =4µm, asphalt coating agent with α resin content of 10%, β resin content of 40% and γ resin content of 50% and D 50 =12um graphite was uniformly mixed at a mass ratio of 3% to obtain mixture A;

[0049] S2. Mixture A is stirred at 80 r / min and 300℃ for 220 min to soften the asphalt and coat it on the graphite surface. After cooling, intermediate product B is obtained.

[0050] S3. Intermediate product B was washed with a 15% polyvinyl alcohol aqueous solution at a mass ratio of 35:1 at 40 r / min and then washed at 120℃ for 4 h to obtain intermediate product C.

[0051] S4. The intermediate product C is carbonized at 1100℃ for 8 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0052] Example 2:

[0053] S1. D 50 =3µm, asphalt coating agent with α resin content of 15%, β resin content of 45% and γ resin content of 40% and D 50 =16um graphite was uniformly mixed at a mass ratio of 1% to obtain mixture A;

[0054] S2. Mixture A is stirred at 120 r / min and 350℃ for 280 min to soften the asphalt and coat it on the graphite surface. After cooling, intermediate product B is obtained.

[0055] S3. Intermediate product B was washed with a 5% polyacrylamide aqueous solution at a mass ratio of 45:1 at 15 r / min and dried at 120℃ for 4 h to obtain intermediate product C.

[0056] S4. The intermediate product C is carbonized at a high temperature of 1250℃ for 9 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0057] Example 3:

[0058] S1. D 50 =5µm, asphalt coating agent with α resin content of 10%, β resin content of 25% and γ resin content of 65% and D 50 Graphite with a density of 8 μm was uniformly mixed at a mass ratio of 4% to obtain mixture A;

[0059] S2. Mixture A is stirred at 60 r / min and 200℃ for 180 min to soften the asphalt and coat it on the graphite surface. After cooling, intermediate product B is obtained.

[0060] S3. Intermediate product B was washed with a 20% concentration of acrylate copolymer aqueous solution at a mass ratio of 30:1 at 25 r / min and dried at 120℃ for 4 h to obtain intermediate product C.

[0061] S4. The intermediate product C is carbonized at 900℃ for 12 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0062] Example 4:

[0063] S1. D 50 =4µm, asphalt coating agent with α resin content of 3%, β resin content of 50% and γ resin content of 42% and D 50 Graphite with a density of 8 μm was uniformly mixed at a mass ratio of 5% to obtain mixture A;

[0064] S2. Mixture A is stirred at 45 r / min and 150℃ for 100 min to soften the asphalt and coat it on the graphite surface. After cooling, intermediate product B is obtained.

[0065] S3. Intermediate product B was washed with a 25% concentration of acrylic polymer aqueous solution detergent at a mass ratio of 20:1 at a speed of 55 r / min and dried at 120°C for 4 h to obtain intermediate product C.

[0066] S4. The intermediate product C is carbonized at 1000℃ for 6 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0067] Comparative Example 1:

[0068] S1. D 50 =4µm, asphalt coating agent with α resin content of 10%, β resin content of 40% and γ resin content of 50% and D 50 =12um graphite was uniformly mixed at a mass ratio of 3% to obtain mixture A;

[0069] S2. The mixture A is carbonized at 1100℃ for 8 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0070] Analysis of the results from Example 1 and Comparative Example 1, and comparison of the SEM images, shows that the graphite product obtained using the preparation method provided by this invention exhibits superior microstructure (…). Figure 1 ) and products obtained by traditional preparation methods ( Figure 2 The results are basically consistent, indicating that the solution provided by this invention does not affect the microstructure of the finished product. A comparison of the TEM images shows that the carbon layer uniformity on the surface of the graphite product obtained using the preparation method provided by this invention is consistent. Figure 3 The product is significantly superior to that obtained by traditional preparation methods. Figure 4 This demonstrates that the solution provided by the present invention can ensure the consistency of carbon layer coating.

[0071] Comparative Example 2:

[0072] S1. D 50 =4µm, asphalt coating agent with α resin content of 10%, β resin content of 40% and γ resin content of 50% and D 50 =12um graphite was uniformly mixed at a mass ratio of 3% to obtain mixture A;

[0073] S2. Mixture A is stirred at 80 r / min and 300℃ for 220 min to soften the asphalt and coat it on the graphite surface. After cooling, intermediate product B is obtained.

[0074] S3. The intermediate product B is carbonized at 1100℃ for 8 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0075] Comparative Example 3:

[0076] S1. D 50 =4µm, asphalt coating agent with α resin content of 10%, β resin content of 40% and γ resin content of 50% and D 50 =12um graphite was uniformly mixed at a mass ratio of 3% to obtain mixture A;

[0077] S2. Mixture A was washed with 15% hexane organic detergent at a mass ratio of 35:1 at 40 r / min and dried at 120°C for 4 h to obtain intermediate product C.

[0078] S3. The intermediate product C is carbonized at 1100℃ for 8 hours, and after cooling and depolymerization, carbon-coated graphite product D is obtained.

[0079] Table 1 compares the performance indicators of the graphite products prepared in Examples 1-4 and Comparative Examples 1-3 of this invention.

[0080] Table 1

[0081]

[0082] Comparing the data of Example 1 and Comparative Example 1, it can be seen that, compared with the traditional preparation method, the graphite product obtained by the method provided by the present invention has significant improvements in terms of rate performance, coking value and agglomeration.

[0083] Comparing the data of Example 1 and Comparative Example 2, it can be seen that although the rate performance was improved by using only the "low temperature softening + high temperature carbonization" scheme, the coking value and caking situation were not effectively improved.

[0084] Comparing the data from Example 1 and Comparative Example 3, and combining them... Figure 5 (SEM image of the graphite product prepared in Comparative Example 3 of this invention) shows that although the coking value and caking condition were significantly improved by using the "organic solvent washing + high temperature carbonization" scheme, the rate performance was not effectively improved, and there was fine powder due to uneven distribution of asphalt on the particle surface.

[0085] In summary, the three-step method of "low-temperature softening + water-soluble washing + high-temperature carbonization" provided by this invention has an obvious improvement effect on the surface coating of graphite products.

Claims

1. A method for graphite coating, the method comprising the following steps: S1. The micron-sized graphite and the asphalt coating agent are uniformly mixed to obtain a mixture A; S2. The mixture A is heated and stirred, and then cooled to obtain an intermediate B; S3. Use a detergent to stir and wash the intermediate product B, and then dry it to obtain the intermediate product C; S4. Carbonizing the intermediate product C at high temperature, cooling and depolymerizing it to obtain the carbon-coated graphite product D.

2. The method according to claim 1, characterized in that The asphalt coating agent in step S1 is composed of α resin (QI), β resin (TI) and γ resin (TS). Preferably, the content of α resin (QI) in the asphalt coating agent is 1% to 15%; and / or, the content of β resin (TI) in the asphalt coating agent is 14% to 50%; and / or, the content of γ resin (TS) in the asphalt coating agent is 35% to 85%.

3. The method according to claim 1 or 2, characterized in that The particle size D50 of the asphalt coating agent is 2 um to 6 um; and / or, the mass ratio of the asphalt coating agent to graphite in step S1 is 0.1 to 10:100, preferably 0.5 to 5:

100.

4. The method according to any one of claims 1 to 3, characterized in that: The heating temperature of the low-temperature stirring in step S2 is T1=100~350°C, preferably 150~350°C; and / or, the heating time of the low-temperature stirring in step S2 is t1=60~300min, preferably 100~280min; and / or, the stirring rate of the low-temperature stirring in step S2 is v1=30~120r / min, preferably 45~120r / min.

5. The method according to any one of claims 1 to 4, characterized in that: In step S3, the detergent contains water and an organic polymer material, and the organic polymer material is preferably one or more of acrylic acid polymer, polyvinyl alcohol, polyacrylamide, and acrylate copolymer. Preferably, the molecular weight of acrylic acid and acrylate polymer is 1 to 5 million, the molecular weight of polyacrylamide is 5 to 20 million, and the molecular weight of polyvinyl alcohol is 80,000 to 120,000.

6. The method according to claim 5, characterized in that The mass proportion of the organic polymer material in the detergent in step S3 is preferably 1 to 45 wt %, and more preferably 5 to 25 wt %.

7. The method according to any one of claims 1 to 6, characterized in that: The mass ratio of the detergent to the intermediate product B in step S3 is (10-100):1, preferably (10-50):1; and / or the stirring rate of the stirring washing in step S3 is v2=10-60r / min, preferably 15-55r / min.

8. The method according to any one of claims 1 to 7, characterized in that: The temperature of high temperature carbonization in step S4 is T2=800-1300°C, preferably 900-1250°C; and / or the time of high temperature carbonization in step S4 is t2=5-15h, preferably 6-12h.

9. Pitch-coated graphite prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Low-temperature fast-charging artificial graphite negative electrode material, preparation method and low-temperature fast-charging battery

    CN113851614A

  • Preparation method and application of graphite negative electrode material

    CN118039828A

  • Coated carbon material, manufacture thereof and lithium secondary battery using the material

    JP2000003708A

Cited By

  • Asphalt shear-coated graphite negative electrode based on waste graphite and preparation method of asphalt shear-coated graphite negative electrode

    CN120527352A